KARAKTERISTIK PENGELOLAAN PEMBELAJARAN KELAS UNGGULAN BERBASIS MUTU STUDI SITUS DI SMP NEGERI 2 PACITAN - KURNIAWAN, WANGSIT (2011)
The purposes of this research are to describe the characteristics of layout, the characteristics of the enrichment of material subject and the characteristics of the relationships between the teacher and the pupils of the excellent classes based on quality at General Junior High School 2 of Pacitan. This is a qualitative research with an ethnography of educational design. This research is taken place General Junior High School 2 of Pacitan. Method of collecting data are using 1) in-depth interview with the principal, teacher of the subject, homeroom teacher and the pupils who follows the excellent classes, 2) observations by visiting continuously to the location and take attention to the situations that factually according with the necessary data of focus and sub focus of the research, 3) collecting another documents which related with focus and sub focus of the research. Data analyze is done with three steps as one piece, consist of data reduction, data display and verification. Data validity is tested by using triangulations technique, such informants triangulation and method triangulation. The result of this research are 1) the school has limited the excellent classes only three classes, with limited pupils, supported with a wider table and separated chair, and also some available media of learning, 2) the teacher gives the enrichment of material subject very fast and also well, the enrichment of material subject leads to the preparation of the National Examination based on several references 3) learning activities happen very fast, very well and also very active because the pupils have good academicals ability. The suggestion of this research are 1) the principal can involve the participation of the educational worker in managing the excellent classes and propose the parents about the excellent classes, 2) teacher of the subject can educate at the excellent classes and also at the regular ones with ripe management, use the facilities and take attention to the pupils' academicals ability, 3) the parents can consider of their children agreement to follow the excellent classes and respect their strength and weakness so they will grow and develop, 4) the pupils can follow the excellent classes very well and yield the objection if they can not do.